INVESTMENT ATTRACTIVENESS OF AGRICULTURAL ENTERPRISES OF THE REGION - Levandivskyi , O.T.; Tsyril , T.V. (The actual problems of regional economy development, 2020)
The presented article clarifies the essence and content of the investment attractiveness of agricultural enterprises in the region. From the point of view of the theory of borrowed funds, the analysis of the capital market uses a neoclassical methodology that examines the factors that determine supply, demand and market equilibrium. It is noted that investment attractiveness is the most important factor in intensifying investment activity in agriculture in the region. Investment attractiveness is considered as a complex socio-economic characteristics of the object of objective and subjective factors, which allows the investor to decide on the feasibility of investing. It was found that the assessment of investment attractiveness of agricultural enterprises in the region should be carried out taking into account the peculiarities of production, the economic situation in which agriculture is currently, as well as the level and effectiveness of state support. Investment attractiveness contains two components: investment potential and investment risk, which embody a number of private indicators. An indispensable condition for optimizing the size of investments and programming the investment effect is to improve the forms and content of investments in their close relationship. Based on the study, it is concluded that under the influence of the same conditions in the region can change both investment potential and investment risk. This conclusion makes the concept of "investment attractiveness" basic and seems to us more reasonable. Areas with low potential and high investment risk are unattractive. But even such regions may be of interest to investors who are focused on investing in a narrow area or have come to high-risk areas in order to make extra profits. Yes, the regions with the lowest risk have the greatest potential and vice versa.